Comments on the Communication Revolution in the United States - Donald Roberts (Communicare)
COMMUNICATION is a social process, the goal of which is to enable people to share meaning and, hopefully, understanding. Thus any change, revolutionary or evolu. tionary, in communication technology Is In- teresting only Insofar as it affects the social exchange of meaning. This paper suggests that we are witnessing not a revolution, but the leading edge of an evolution. It seems to be process of supplementation in which the new technologies operate in concert with the old.